Characterization, Breeding and Selection of Rice Germplasm Panels Adapted to Low Soil Phosphorous and Nitrogen Environments in Kenya: An Advanced Study - Kimani J. M; Lee, Sang Bok; Kang Kyung – HO; Sikuku, Phoebe Anyango; Gichuhi, Emily Waringa; Kilonzo, Mutiga Samuel; Thuranira, David Mwongera; Ondiko, Clotilda Nekesa; Wasilwa, Lusike; Kalume, John Kirao; Tongoona P.; Derera J. (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
Rice breeding efforts in Kenya have slowly been taking place to develop locally adapted high-yielding varieties with desirable eating qualities. Soil nitrogen (N) and phosphorus (P) deficiencies are among the major constraints constrictive to rice productivity globally, especially in resource-poor farming systems which were traditionally self-sustaining through slash and burn. There is therefore need to develop rice genotypes with enhanced root architecture that help them tolerate low soil N and P conditions. This work aimed at developing rice genotypes with enhanced tolerance to low N and P conditions through targeted breeding approaches that include hybridization, evaluations and recent works on rice research space. A diverse panel of rice germplasm obtained from CIAT Colombia as accessions and breeds for rainfed conditions were screened under controlled and field conditions to identify traits associated with nutrient use efficiency and generate information in this discipline. A total of 389 accessions and a local cultivar Duorado precoce were evaluated in a simple 30 × 13 alpha lattice design with two replications under four soil experimental environments (N-P-, no N or P application; N-P+, P applied; N+P-, N applied and N+P+, both N and P applied) at the rate of 60 kg P and 90 kg N ha-1. Data was recorded on Days to heading, anthesis and maturity (days), P and N tolerance, plant height (cm), above ground biomass (g), number of panicles (absolute numbers per ten plants), days to maturity (days), 1000 grain weight (g), and grain yield (kg ha-1). The genotypes and environments were highly significant for all the traits studied. The degree of genetic determination (H2) ranged from 6.8% for P tolerance to 36.5% for above ground biomass. The phenotypic coefficient of variation of genotypes ranged from 14.3% for days to maturity to 159.7% for top biomass. The genetic advance (GA) ranged from 0.2 for phosphorous tolerance to 1080.5 for grain yield, while the genetic advance expressed as a percent of the mean was 5.7% for days to maturity and 87.9% for top biomass. The top biomass seems to be a highly heritable trait and simple phenotypic selection is possible. The ten characters studied had wide variability under the four environments with days to maturity ranging from 188 for genotype ARCCU1Fa1-L4P3-HB under N+P+ to 177 for genotype CT16333(1)-CA-1-M under N-P- condition. The highest yielding genotype was CT16328-CA-18-M under N-P- with 5916 kg ha-1. The germplasm showed variability for low soil N and P adaptation, and hence improvement was possible to take advantage of the vast unexploited both rainfed lowland and upland environments for increased rice productivity to meet food-feed and nutritional households and national security in Kenya. There was high variability among the genotypes to warrant rice improvement for yield. Field trials conducted at AfricaRice research fields in Senegal have revealed significant yield improvements in the newly developed lines under nutrient deficient, toxic elements and problem soil environmental conditions. This study underscores the potential of breeding for nutrient-efficient rice varieties as a sustainable economic solution that reduces the need for fertilizers used to enhance productivity in nutrient-poor soils, contributing to food-feed and nutritional security in sub-Saharan Africa.